Drug Eluting Stents & Coronary Angiography - Rawat, Bharat; Poudel, PR; Mulmi, Smriti (Nepalese Heart Journal, 2006)
Twenty-five years ago, a young German physician, Andreas Gruentzig, inserted a catheter into a 38-year-old man's coronary artery, inflated a tiny balloon the doctor had fashioned in his own kitchen, successfully opening a blockage and restoring blood flow to a human heart. This event set a cascade of newer invention.